Corr2d: Implementation of two-dimensional correlation analysis in R - Geitner, Robert; Fritzsch, Robby; Popp, Jürgen; Bocklitz, Thomas W. (Journal of Statistical Software, 2019)
In the package corr2D two-dimensional correlation analysis is implemented in R. This paper describes how two-dimensional correlation analysis is done in the package and how the mathematical equations are translated into R code. The paper features a simple tutorial with executable code for beginners, insight into the calculations done before the correlation analysis, a detailed look at the parallelization of the fast Fourier transformation based correlation analysis and a speed test of the calculation. The package corr2D offers the possibility to preprocess, correlate and postprocess spectroscopic data using exclusively the R language. Thus, corr2D is a welcome addition to the toolbox of spectro-scopists and makes two-dimensional correlation analysis more accessible and transparent.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D correlation; Corr2D; Correlation analysis; R; R package; Spectroscopy